2018
DOI: 10.1021/acschemneuro.8b00023
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Sequencing of Salsolinol Synthase, an Enzyme Catalyzing Salsolinol Biosynthesis

Abstract: Salsolinol (1-methyl-6,7-dihydroxy-1,2,3,4-tetrahydroisoquinoline), a derivate of dopamine, is suspected to be the most probable neurotoxin in the degeneration of dopaminergic neurons. Numerous hypotheses regarding its pathophysiological roles have been raised, especially related to Parkinson's disease and alcohol addiction. In the mammalian brain, salsolinol may be enzymatically synthesized by salsolinol synthase from dopamine and acetaldehyde. However, the direct evidence of its biosynthesis was still missin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
28
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 45 publications
(81 reference statements)
1
28
0
1
Order By: Relevance
“…For many years, mostly due to limitations of the available analytical methods, it was thought that (R)-salsolinol should be the only enantiomer present in human brain tissue. In this respect, it has been reported that the R-enantiomer predominates in urines of healthy volunteers, whereas the S-enantiomer predominates in port wine and possibly in other beverages and foods, suggesting that salsolinol present in human bodies could have, at least partially, an endogenous enzymatic origin (Chen et al 2018), as previously suggested by Collins et al (1990). These experiments have shown that co-administration of small doses of L-DOPA with the ethanol/liquid diet led to an increased striatal concentration of salsolinol as shown in Fig.…”
Section: Ethanol and Tiqsmentioning
confidence: 53%
See 3 more Smart Citations
“…For many years, mostly due to limitations of the available analytical methods, it was thought that (R)-salsolinol should be the only enantiomer present in human brain tissue. In this respect, it has been reported that the R-enantiomer predominates in urines of healthy volunteers, whereas the S-enantiomer predominates in port wine and possibly in other beverages and foods, suggesting that salsolinol present in human bodies could have, at least partially, an endogenous enzymatic origin (Chen et al 2018), as previously suggested by Collins et al (1990). These experiments have shown that co-administration of small doses of L-DOPA with the ethanol/liquid diet led to an increased striatal concentration of salsolinol as shown in Fig.…”
Section: Ethanol and Tiqsmentioning
confidence: 53%
“…As racemic mixture of enantiomers, salsolinol can be formed non-enzymatically by the Pictet-Spengler reaction of DA with acetaldehyde ( Fig. 2) (Cohen and Collins 1970) or from pyruvic acid followed by decarboxylation (Dostert et al 1988;Chen et al 2018). Whilst, the stereo-selective enzymatic synthesis from DA via (R)-salsolinol synthase is supposed to generate the (R)-enantiomer ( Fig.…”
Section: Ethanol and Tiqsmentioning
confidence: 99%
See 2 more Smart Citations
“…Anal. Calcd for C23 H 27 N 3 O 2 S (409.55): C, 67.45; H, 6.65; N, 10.26; S, 7.83%. Found: C, 67.33; H, 6.55; N, 10.16; S, 7.71%.…”
mentioning
confidence: 99%